Fahr disease discovered after closed head injury - Yakhya Cisse; Abdoulaye Diop; Ansoumane Donzo; Roger Ilunga Mulumba; Louncény Fatoumata Barry; Natatcha Maria Diakaoé Sambou; Jean Michel Nzisabira; Momar Codé Ba (Elsevier, 2022)
Fahr's disease is a rare anatomical-clinical entity, characterised by the presence of multiple bilateral and symmetrical intracerebral calcifications, located in the basal ganglia, most often associated with disorders of phospho calcium metabolism. Hypoparathyroidism, whether primary or postoperative, is the most common abnormality. Hyperparathyroidism is exceptionally reported as a cause of Fahr's syndrome. We report the case of a 14 year old boy followed for epilepsy with the notion of a regression of psychological acquisitions, who consulted because of a cranioencephalic trauma revealing a Fahr's disease with the particularity of the existence of a hyperparathyroidism. From this case report, we can deduce that cranioencephalic trauma can be a rare circumstance of discovery of Fahr's disease.